2020
DOI: 10.1038/s41535-020-0248-y
|View full text |Cite
|
Sign up to set email alerts
|

Kondo scenario of the γ–α phase transition in single crystalline cerium thin films

Abstract: The physical mechanism driving the γ–α phase transition of face-centre-cubic (fcc) cerium (Ce) remains controversial until now. In this work, high-quality single crystalline fcc–Ce thin films were grown on Graphene/6H-SiC(0001) substrate, and explored by XRD and ARPES measurement. XRD spectra showed a clear γ–α phase transition at Tγ−α ≈ 50 K, which is retarded by strain effect from substrate comparing with Tγ−α (about 140 K) of the bulk Ce metal. However, APRES spectra did not show any signature of α-phase em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 50 publications
5
7
0
Order By: Relevance
“…5 a), which is very different from the expected γ–α transition at ~150 K for bulk Ce 34 . We mention that the similar suppression of the γ–α transition in epitaxial Ce films has also been reported 29 , 35 , although the percentage of the α-phase at low temperature differs due to different growth conditions.
Fig.
…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…5 a), which is very different from the expected γ–α transition at ~150 K for bulk Ce 34 . We mention that the similar suppression of the γ–α transition in epitaxial Ce films has also been reported 29 , 35 , although the percentage of the α-phase at low temperature differs due to different growth conditions.
Fig.
…”
Section: Resultssupporting
confidence: 81%
“…2 c), which simply treats 4 f electrons as core electrons; near E F , however, the Kondo resonance peaks emerge and the c – f hybridization leads to the characteristic reversed-U-shaped band expected for a hole-band crossing. A simple simulation (with a hybridization strength V = 70 meV adapted from a recent study 29 ) can reproduce the experimental results well (green dashed curves in Fig. 2 c).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Upon annealing to intermediate temperature, an ordered single-crystal Ce film can be obtained (P1), as determined by streaky diffraction pattern in RHEED and clear dispersive conduction bands in the ARPES spectra. This phase was observed in previous ARPES studies and identified as the γ phase [29,30,32]. Compared to the P0 phase, the lower Hubbard band shifts to slightly lower energy (-1.9 eV) and remains dispersionless, and the Kondo resonance peaks near E F become sharper and more pronounced.…”
Section: Tuning Across the Bandwidth-control Osd Of 4f Electronssupporting
confidence: 61%
“…Some theoretical studies further pointed to the importance of the interplay between two mechanisms [19,20,21,22,23]. While previous photoemission studies provided compelling evidences that the Kondo effect plays an important role in the electronic structure of Ce [24,25,26,27,28,29,30], no spectroscopic evidence supporting the Mott scenario has ever been reported. Unambiguous identification of the bandwidth-control 4f delocalization is experimentally challenging, as the coexisting Kondo screening could lead to somewhat similar itinerant 4f bands.…”
mentioning
confidence: 99%